БИЛИМЛЕНДИРИЎ ТАРАЎЫНДАҒЫ РЕФОРМАЛАР ЖАСЛАРЫМЫЗДЫҢ ТӘЛИМ-ТӘРБИЯСЫНА ХЫЗМЕТ ЕТЕДИ - Қаллибеков, Т. (FAN va JAMIYAT, 2018)
The article deals with the issues of reforming in the system of education, the analysis of reforms of non-governmental educational establishments, in particular.